Learn C# 8 a beginner's guide to building a solid foundation for C# programming - Bancila, Marius (Packt Publishing, 2020)
Learning C# 8 covers in detail the most important building blocks of C# that will help you learn every aspect of C# programming with an easy learning curve. With extensive coverage of the topics explained with the real-world examples, you will gain an in-depth knowledge of practical details involved in software development using C#.